The Effect of Syllabic Method on Reading Difficulties in Second-Grade Students of SDN 026 Banua - Baru, Polewali Mandar Regency, West Sulawesi Province - Sri Nurazizah; Nurhayati Selvi; Ira Irviana (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the effect of the syllabic method on reading difficulties in grade II students at SD Negeri 026 Banua – Baru, Polewali Mandar Regency, West Sulawesi Province. The research method used is quantitative with the type of pre-experimental research with a one-group pretest-posttest design. The research location was at SD Negeri 026 Banua – Baru, Polewali Mandar Regency, West Sulawesi Province, with a sample of 20 grade II students consisting of 12 boys and 8 girls. Data collection was carried out using a pretest test and a posttest test. Instrument testing uses validity and reliability. Data analysis techniques used descriptive statistical analysis and inferential statistical analysis, and hypothesis testing in the form of a paired sample T-test. Based on the research that has been done, the results obtained are hypothesis testing paired sample t-test showing that there is an effect of the syllabic method on reading difficulties in class II students at SD Negeri 026 Banua – Baru, Polewali Mandar Regency, West Sulawesi Province, as evidenced by the results of the paired test. Sample t-test obtained a value of 0.001 < 0.05, in other words, this study has a significant effect. Keywords: Syllabic Method; Difficulty Reading.